A New Architecture for Printable Photovoltaics Overcoming Conventional Module Limits. (16th December 2013) - Kang, Hongkyu; Hong, Soonil; Back, Hyungcheol; Lee, Kwanghee
Abstract : A new architecture for manufacturing large‐area polymer solar cells that does not produce concomitant aperture and Ohmic losses is presented. By introducing the innovative concept of metal‐filamentary nanoelectrodes, which are vertically formed inside the main active layers, loss‐free, widely expandable solar cells with the highest relative power conversion efficiency (ca. 90%) in organic photovoltaic systems are demonstrated.